The effects of physiotherapy treatments on dysphagia in Parkinson’s disease: A systematic review of randomized controlled trials - Xin Wen; Zicai Liu; Xuejin Liu; Yang Peng; Huiyu Liu (Brain Research Bulletin, 2022)
Background: The prevalence of swallowing disorders in Parkinson’s disease (PD) is relatively high. Different physiotherapy interventions for swallowing disorders are available but there is a lack of evidence-based medicine for their effectiveness in PD. Objective: The purpose of this systematic review was to investigate the effects of different physiotherapy interventions on dysphagia in PD. Methods: This systematic review was conducted according to PRISMA guidelines. We methodically searched databases including PubMed, PEDro, Cochrane Library, Embase, and Web of Science. Studies of any language published up to March 2022 were searched. Randomized controlled trials (RCTs) of non-pharmacological treatment for dysphagia in PD were selected in strict accordance with our exclusion and inclusion criteria. Results: In total, we identified and included 10 RCTs in patients with PD undergoing dysphagia. This review involved seven rehabilitation treatments, including acupuncture, expiratory muscle strength training (EMST), repetitive transcranial magnetic stimulation (rTMS), video-assisted swallowing therapy (VAST), electrical stimulation, and speech and language therapy (SLT). Conclusion: For physiotherapy treatments, including acupuncture, EMST, high-frequency rTMS and VAST may be effective treatments for dysphagia in patients with PD. However, there was not enough evidence that electrical stimulation has therapeutic effects on dysphagia in patients with PD.